Isotrias huemeri sp. n. (Lepidoptera Tortricidae) from southern Appennine (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Tortricidae, lsotrias huemeri sp. n., is described; the species is close to Isotrias rectifasciana (Haworth). The differences between the two species are in the pattern of wings as in the male and female genitalia.
Keywords: lsotrias huemeri; Lepidoptera Tortricidae; new species; Southern Appennine